Uji Efektivitas Formula Pedikulosida Berbahan Aktif Minyak Atsiri Terhadap Mortalitas Kutu Kepala (Pediculus humanus capitis De Geer) Secara In Vitro - Tanendri Arrizqiyani (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2018)
Pediculosis is a disease caused by Pediculus humanus capitis de Geer or often called head lice which is an obligate ectoparasite in the human head. The prevalence of pediculosis is quite high and there are reports of resistance and negative side effects regarding the use of synthetic pediculosides trigger research and development of vegetable pediculosides. This study aims to examine the effectiveness of the formula of pediculoside with active ingredients of essential oils on head lice mortality in vitro. The study was conducted by testing 3 formulas with variations in the composition of essential oils made from cassava oil, fennel oil, lemon oil, water and vegetable glycerine. Comparison of the ingredients in formula A is 10%, 10%, 5%, 50% and 20%; formula B is 5%, 15%, 5%, 50% and 20%; while formula C is 15%, 5%, 5%, 50% and 20%. The test method is an experiment with a completely randomized design. The test is done by placing 10 adult head lice on filter paper which has been saturated with a formula made in a petri dish. Mortality of head lice is observed based on time. Test results data will be compared with negative controls and positive controls in the form of testing using permethrin-active pediculoside drugs. The results showed that the pediculoside formula A, B and C had a high mortality rate which caused 100% of the deaths of head lice tested in less than 5 minutes. Statistically there is a significance to the results of testing formulas A, B, and C when compared to controls. Based on the results of multiple statistical statistics, it was found that formula C was the most effective as a pediculoside formula